Risk factors for loss to follow up of pelvis and acetabular fractures. Issue 11 (November 2022) - Cantrell, Colin K; Versteeg, Gregory H; Goedderz, Cody J; Johnson, Daniel J; Tanenbaum, Joseph E; Carney, John J; Bigach, Stephen D; Williams, Joel C; Stover, Michael D; Butler, Bennet A
Abstract: Introduction: Pelvic and acetabular fracture incidence is increasing worldwide for more than four decades. There is currently no evidence examining risk factors for loss to follow up in patients with these injuries. Methods: Patients presenting with pelvic and/or acetabular fractures at our institution between 2015 and 2020 were included. Demographic, injury, treatment, and follow up information was included. Excluded patients were those who sustained a pathologic fracture, has a course of treatment prior to transfer to our centre, or expired prior to discharge. Results: 446 patients, 263 with a pelvic ring injury, 172 with an acetabular fracture, and 11 with combined injuries were identified. 271 (61%) of patients in our cohort followed up in Orthopaedic clinic ( p  = 0.016). With an odds ratio of 2.134, gunshot wound mechanism of injury was the largest risk factor for loss to follow up ( p  = 0.031) followed by male sex (OR= 1.859) and surgery with general trauma surgery (OR=1.841). The most protective risk factors for follow up with Orthopaedic surgery were operatively treated pelvic and acetabular fractures (OR=0.239) and Orthopaedic Surgery as the discharging service (OR=0.372). Discussion: Numerous risk factors exist for loss to follow up including male sex, ballistic mechanism, and discharging service. Investigation into interventions to improve follow up in these patients are warranted.